Constraining the Carbon Budget of Peat Ecosystems: Application of Stoichiometry and Enthalpy Balances. Issue 10 (11th October 2022) - Worrall, Fred; Boothroyd, Ian. M.; Clay, Gareth D.; Moody, Catherine S.; Heckman, Katherine; Burt, Tim P.; Rose, Rob
Abstract: We consider how the stoichiometry and energy content of organic matter reservoirs and fluxes through and from a peatland enable the fluxes and storage of carbon within a peatland to be constrained. We include the elemental composition of the above‐ and below‐ground biomass, litter, the peat profile, and the dissolved and particulate organic matter within a blanket bog in northern England for which the C budget has previously been measured. The study shows, based only on the elemental composition, and calculation of oxidation and energy contents, that: (a) Dissolved organic carbon (DOC) in first‐order streams is significantly more oxidized than in peat pore water but that there was no significant difference in organic carbon oxidation state down the peat profile; (b) The occurrence and speciation of N uptake and release in the peatland with N used and recycled can be predicted; (c) The relatively high oxidation state of DOC in stream water acts as an endpoint for peat‐forming reactions; (d) Methanogenesis does not result in deep peat formation as its requirement for energy consumes too much organic matter to form residual peat at depth; (e) Sulfate reduction does occur during the formation of deep peat; (f) Organic matter elemental composition could be constrained to within three bounding equations though the proportions of carbon species could not be specified. (g) The formation of deep peat in this catchment could only be achieved if the dissolved organic matter (DOM) in the peat pore water is the dominant electron acceptor and energy source in the production of residual organic matter; however, it is unclear as to the flux of DOM up or down the peat profile. Plain Language Summary: Peatlands are a vital terrestrial carbon store and so understanding their carbon budget has been a common measure of the health of those peatlands. Measuring carbon budgets a long and expensive process. However, we propose that the reactions of organic matter in peatlands must be constrained, like all chemical reactions, by stoichiometry and by enthalpy. Using elemental analysis of peat organic matter this study could reconstruct the C budget of a peatland and show which reactions are the most important. Key Points: Study applies rules of stoichiometry and enthalpy balance to understand carbon budgets of peatlands Methanogenesis does not result in deep peat formation as it requires too much energy to form residual organic matter at depth Deep peat formation could only be achieved if the dissolved organic matter in the peat pore water was the dominant electron acceptor